The Origin and Early Evolution of Life: Prebiotic Chemistry of Biomolecules - Fiore, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Studying the origin of life is one of man's greatest achievements over the last sixty years. The fields of interest encompassed by this quest are multiple and interdisciplinary: chemistry, physics, biology, biochemistry, mathematics, geology but also statistics, atmospheric science, meteorology, oceanography, and astrophysics. Recent scientific discoveries, such as water on Mars and the existence of super-Earths with atmospheres similar to primordial Earth, have pushed researchers to simulate prebiotic conditions in explaining the abiotic formation of molecules essential to life. This collection of articles offers an overview of recent discoveries in the field of prebiotic chemistry of biomolecules, their formation and selection, and the evolution of complex chemical systems.